On the corner : African American intellectuals and the urban crisis - Matlin, Daniel (Harvard University Press, 2013)
In July 1964 when a Harlem riot shifted attention to the crisis in northern cities, African American intellectuals were thrust into the spotlight as interpreters of black urban life to white America. On the Corner revisits the moment when black urban life became, for these intellectuals, "the topic that is reserved for blacks."